1980
DOI: 10.1007/bf02312547
|View full text |Cite
|
Sign up to set email alerts
|

Inherited metabolic disease in laboratory animals: a review

Abstract: Research on the screening for and study of animal models of inherited metabolic disease is reviewed. It is emphasized that an animal model, to be of value, must be an inherited deficiency of the same enzyme as the one deficient in the human syndrome. If this criterion is adhered to there is a remarkable identity in aetiology between animal and man. Specific examples of inherited metabolic disease in laboratory animals are described for: amino acid metabolism; lysosomal storage diseases, carbohydrate metabolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…An animal model of inherited metabolic disease can be of full value only if the inherited enzyme deficiency is the same as that marking the human condition (Bulfield, 1980). However, even if a basic genetic defect is similar in animals and man, the phenotypic expression in both species may" not correspond due to differences in the interaction of environmental and genetical factors (Winchester,, 1982).…”
Section: Comparison Of Animal and Human Glycogen Storage Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…An animal model of inherited metabolic disease can be of full value only if the inherited enzyme deficiency is the same as that marking the human condition (Bulfield, 1980). However, even if a basic genetic defect is similar in animals and man, the phenotypic expression in both species may" not correspond due to differences in the interaction of environmental and genetical factors (Winchester,, 1982).…”
Section: Comparison Of Animal and Human Glycogen Storage Diseasementioning
confidence: 99%
“…The value of animal models for the study of human inherited metabolic disease has recently been discussed (Bulfield, 1980;Winchester, 1982). It was stressed that this value strongly depends on the homology of the animal condition and the respective human one.…”
mentioning
confidence: 99%
“…Seven inherited diseases that result in disorders of metal metabolism have been recognized in the mouse (Bulfield, 1980). Wiener (1979) has reported significant differences in plasma and liver copper content between breeds of sheep, as well as differences in susceptibility to copper poisoning.…”
Section: Discussionmentioning
confidence: 98%
“…Emphasis will be placed on human aspects and in particular on those features related to inherited metabolic disorders. However, a cautionary note must be added, for many of the studies reported here have by necessity used other animals, and species differences do frequently arise (Bulfield, 1980).…”
mentioning
confidence: 96%
“…To date, there are seven inherited disorders of trace metal metabolism known in animal species, mainly in the mouse (Bulfield, 1980). These all involve disorders in metal metabolism or transport.…”
mentioning
confidence: 99%